Co-administration of dexamethasone increases severity and accelerates onset day of neutropenia in bladder cancer patients on methotrexate, vinblastine, adriamycin and cisplatin chemotherapy: a retrospective cohort study - Itai, Shingo (J Pharm Health Care Sci, 2017)
BACKGROUND: Bladder cancer patients receiving methotrexate, vinblastine, adriamycin and cisplatin (MVAC) chemotherapy are co-administered with dexamethasone as an anti-emetic. We examined whether or not dexamethasone affects the severity and onset day of MVAC-induced severe neutropenia. METHODS: This was a retrospective study of bladder cancer patients treated with MVAC chemotherapy with or without dexamethasone as an antiemetic at Kanazawa University Hospital during January 2005 - December 2009. Patients were categorized into three groups; no dexamethasone use (Dex (−)), dexamethasone on day 2 (Dex 1 day), and dexamethasone on days 2, 3 and 4 (Dex multiday). We evaluated the incidence of grade 3/4 neutropenia and the day of onset of first severe neutropenic episode during the first course of MVAC chemotherapy. Logistic regression was used to investigate whether co-administration of dexamethasone was a risk factor for severe neutropenia. RESULTS: Episodes of grade 3/4 neutropenia occurred in 3 out of 6 (50.0%), 11 out of 12 (91.7%) and 6 out of 6 (100%) patients in the Dex (−), Dex 1 day, and Dex multiday groups, respectively. The appearance day of first severe neutropenia in the Dex multiday group (13.2 ± 1.0) was significantly accelerated compared to the Dex (−) group (17.7 ± 2.1). Univariate logistic regression analysis revealed that dexamethasone is a risk factor for severe neutropenia (OR 17.0; 95%CI: 1.3–223.1). CONCLUSIONS: Co-administration of dexamethasone for anti-emesis brings forward the first appearance of neutropenia, and increases the severity of neutropenia, in bladder cancer patients receiving MVAC chemotherapy.